Вы находитесь на странице: 1из 9

1

2x 3 y + z 1 = 0
L:
.

x+ y z+ 1= 0

1. L.
2. L , (1;-1;0)
L.
3. L L.
4. , L L .
L:

x
y+2 z
=
= .
1
1
0

5. L L.
6. , L
L.
7. P P, P
L L.
8. L L.
9. 2 x + y z + 1 = 0.
10. L 2 x + y z + 1 = 0.

2x + 3 y + z 1 = 0
L:
.

x+ y z+ 1= 0

1. L.
2. L , (1;-1;0)
L.
3. L L.
4. , L L .
L:

x
y+2 z
=
= .
1
1
0

5. L L.
6. , L
L.
7. P P, P
L L.
8. L L.
9. 2 x + y z + 1 = 0.
10. L 2 x + y z + 1 = 0.

2x + 3 y + z 1 = 0
L:
.

x+ y z+ 1= 0

1. L.
2. L , (1;-1;0)
L.
3. L L.
4. , L L .
L:

x
y+2 z
=
= .
1
1
0

5. L L.
6. , L
L.
7. P P, P
L L.
8. L L.
9. 2 x + y z + 1 = 0.
10. L 2 x + y z + 1 = 0.

2x 3 y + z 1 = 0
L:
.

x+ y z+ 1= 0

1. L.
2. L , (1;-1;0)
L.
3. L L.
4. , L L .
L:

x
y+2 z
=
= .
1
1
0

5. L L.
6. , L
L.
7. P P, P
L L.

8. L L.
9. 2 x + y z + 1 = 0.
10. L 2 x + y z + 1 = 0.

2x 3 y + z 1 = 0
L:
.

x y z+ 1= 0

1. L.
2. L , (1;-1;0)
L.
3. L L.
4. , L L .
L:

x
y+2 z
=
= .
1
1
0

5. L L.
6. , L
L.
7. P P, P
L L.
8. L L.
9. 2 x + y z + 1 = 0.
10. L 2 x + y z + 1 = 0.

2x 3 y + z 1 = 0
L:
.

x+ y z+ 1= 0

1. L.
2. L , (1;-1;0)
L.
3. L L.
4. , L L .
L:

x
y+2 z
=
= .
1
1
0

5. L L.

6. , L
L.
7. P P, P
L L.
8. L L.
9. 2 x + y z + 1 = 0.
10. L 2 x + y z + 1 = 0.

2x + 3 y + z 1 = 0
L:
.

x+ y z+ 1= 0

1. L.
2. L , (1;-1;0)
L.
3. L L.
4. , L L .
L:

x
y+2 z
=
= .
1
1
0

5. L L.
6. , L
L.
7. P P, P
L L.
8. L L.
9. 2 x + y z + 1 = 0.
10. L 2 x + y z + 1 = 0.

2x + 3 y + z 1 = 0
L:
.

x+ y z+ 1= 0

1. L.

2. L , (1;-1;0)
L.
3. L L.
4. , L L .
L:

x
y+2 z
=
= .
1
1
0

5. L L.
6. , L
L.
7. P P, P
L L.
8. L L.
9. 2 x + y z + 1 = 0.
10. L 2 x + y z + 1 = 0.

2x 3 y + z 1 = 0
L:
.

x+ y z+ 1= 0

1. L.
2. L , (1;-1;0)
L.
3. L L.
4. , L L .
L:

x
y+2 z
=
= .
1
1
0

5. L L.
6. , L
L.
7. P P, P
L L.
8. L L.
9. 2 x + y z + 1 = 0.
10. L 2 x + y z + 1 = 0.

10

2x 3 y + z 1 = 0
L:
.

x y z+ 1= 0

1. L.
2. L , (1;-1;0)
L.
3. L L.
4. , L L .
L:

x
y+2 z
=
= .
1
1
0

5. L L.
6. , L
L.
7. P P, P
L L.
8. L L.
9. 2 x + y z + 1 = 0.
10. L 2 x + y z + 1 = 0.

11

2x 3 y + z 1 = 0
L:
.

x+ y z+ 1= 0

1. L.
2. L , (1;-1;0)
L.
3. L L.
4. , L L .
L:

x
y+2 z
=
= .
1
1
0

5. L L.
6. , L
L.
7. P P, P
L L.
8. L L.
9. 2 x + y z + 1 = 0.
10. L 2 x + y z + 1 = 0.

12

2x + 3 y + z 1 = 0
L:
.

x+ y z+ 1= 0

1. L.
2. L , (1;-1;0)
L.
3. L L.
4. , L L .
L:

x
y+2 z
=
= .
1
1
0

5. L L.
6. , L
L.
7. P P, P
L L.
8. L L.
9. 2 x + y z + 1 = 0.
10. L 2 x + y z + 1 = 0.

13

2x + 3 y + z 1 = 0
L:
.

x+ y z+ 1= 0

1. L.
2. L , (1;-1;0)
L.
3. L L.
4. , L L .
L:

x
y+2 z
=
= .
1
1
0

5. L L.
6. , L
L.
7. P P, P
L L.
8. L L.

9. 2 x + y z + 1 = 0.
10. L 2 x + y z + 1 = 0.

14

2x 3 y + z 1 = 0
L:
.

x+ y z+ 1= 0

1. L.
2. L , (1;-1;0)
L.
3. L L.
4. , L L .
L:

x
y+2 z
=
= .
1
1
0

5. L L.
6. , L
L.
7. P P, P
L L.
8. L L.
9. 2 x + y z + 1 = 0.
10. L 2 x + y z + 1 = 0.

15

2x 3 y + z 1 = 0
L:
.

x y z+ 1= 0

1. L.
2. L , (1;-1;0)
L.
3. L L.
4. , L L .
L:

x
y+2 z
=
= .
1
1
0

5. L L.

6. , L
L.
7. P P, P
L L.
8. L L.
9. 2 x + y z + 1 = 0.
10. L 2 x + y z + 1 = 0.